Visual environment recognition for robot path planning using template matched filters - Orozco Rosas, Ulises; Picos, Kenia; Diaz Ramírez, Víctor; Montiel, Oscar; Sepúlveda, Roberto (My University, 2017)
A visual approach in environment recognition for robot navigation is proposed. This work includes a template matching filtering technique to detect obstacles and feasible paths using a single camera to sense a cluttered environment. In this problem statement, a robot can move from the start to the goal by choosing a single path between multiple possible ways. In order to generate an efficient and safe path for mobile robot navigation, the proposal employs a pseudo-bacterial potential field algorithm to derive optimal potential field functions using evolutionary computation. Simulation results are evaluated in synthetic and real scenes in terms of accuracy of environment recognition and efficiency of path planning computation. RESUMEN Se propone un enfoque visual en el reconocimiento del entorno para la navegación de robots. Este trabajo incluye una técnica de filtrado de coincidencia de plantillas para detectar obstáculos y caminos factibles utilizando una sola cámara para detectar un entorno desordenado. En este enunciado del problema, un robot puede moverse desde el principio hasta la meta eligiendo un solo camino entre múltiples caminos posibles. Con el fin de generar una ruta eficiente y segura para la navegación de robots móviles, la propuesta emplea un algoritmo de campo potencial pseudobacteriano para derivar funciones de campo potencial óptimas utilizando computación evolutiva. Los resultados de la simulación se evalúan en escenas sintéticas y reales en términos de precisión del reconocimiento del entorno y eficiencia del cálculo de la planificación de rutas.
ads
Keywords: Visual; robot path; Campus Tijuana